Chapter Fonti europee e russe in Ruslan e Ljudmila di Puškin - STRANO, Giacoma (Biblioteca di Studi Slavistici, 2019)
In Ruslan i Ljudmila, Puškin arranges European and Russian sources in a particular dialectic system that may be seen as illustrative of his poetics. Specifically, the poema's dedication and its theme recall the novellas of Giambattista Casti; the narrating cat in the prologue may be connected to the celebrated fables of Tieck, Perrault, and Hoffmann; events and battle scenes in the text derive from the chronicles; and Ruslan's deeds from lubočnaja literatura. Images of the "lascivious East", together with other eroticized descriptive passages point to the well-known models of Moore, Byron, Goethe, and Parny, while in the weave of Ruslan i Ljudmila's individual cantos, we find quotations from Macpherson, Ozerov, and Tasso.